THE EFFECT OF ECONOMIC PRESSURE AND QUALITY OF LIFE ON THE QUALITY OF FAMILY PARENTING WITH STUNTING CHILDREN: Pengaruh Tekanan Ekonomi Dan Kualitas Hidup Terhadap Kualitas Pengasuhan Keluarga Dengan Anak Stunting - Zoelianafasa, Shafa Isnanda; Herawati, Tin (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Currently, Indonesia is still facing a health problem, namely stunting. This condition can be caused by various factors, both directly and indirectly. Indirect causes of stunting that are currently of common concern include family conditions, both economically, socially, and the quality of parenting given to children. The purpose of this research is to analyze the effect of economic pressure and quality of life on the quality of family parenting with stunted children. This research involved 69 mothers with stunted children aged 2-5 years. The research location is in Bubulak Village, Bogor City, West Java. Sampling was done using non-probability sampling using purposive sampling technique. The correlation test shows that economic pressure has a significant correlation with the quality of life and quality of parenting. Quality of life is significantly related to the quality of parenting. The results of the regression test show that economic pressure does not affect the quality of parenting, while the child's age affects the quality of parenting, as does the quality of life which has a significant positive effect on the quality of parenting.